International Travel in Unsettled Times - Mickie Swisher (EDIS, 2003)
Many of us must travel for our work. Others of us simply want to travel. While you do need to take certain basic precautions when traveling outside the United States, you can travel safely in today’s world. This document is FCS9196, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611. First published: May 2003.